2023
DOI: 10.1186/s13643-023-02321-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dyslipidemia and diabetic retinopathy in patients with type 2 diabetes mellitus: a systematic review and meta-analysis

Zhaoping Li,
Yuan Yuan,
Qianjin Qi
et al.

Abstract: Background Diabetic retinopathy (DR) affects more than 80% of patients with diabetes. However, literature on the association between serum lipids and DR in patients with type 2 diabetes mellitus (T2DM) is inconsistent. Hence, in this study, we aimed to investigate the relationship between baseline serum lipids and the incidence of DR in patients with T2DM. Methods We searched relevant articles in the PubMed, Embase databases, and the Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The above criteria have been applied in previous literatures ( 18 , 20 ). In addition, we examined these SNPs on the Phenoscanner V2 website ( http://www.phenoscanner.medschl.cam.ac.uk/ ) to evaluate whether they are related to common confounders for DR, such as Type 1 Diabetes ( 5 ), Type 2 Diabetes (T2D) ( 21 ), Diabetic nephropathy (DN) ( 22 ), HbA1c ( 6 ), blood pressure ( 8 ), fasting glucose ( 6 ), fasting insulin ( 23 ), Total Cholesterol ( 7 ), Body Mass Index ( 24 ) and smoking ( 25 ). SNPs related to the above confounders ( p < 1×10 –5 ) were excluded to satisfy the MR assumptions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above criteria have been applied in previous literatures ( 18 , 20 ). In addition, we examined these SNPs on the Phenoscanner V2 website ( http://www.phenoscanner.medschl.cam.ac.uk/ ) to evaluate whether they are related to common confounders for DR, such as Type 1 Diabetes ( 5 ), Type 2 Diabetes (T2D) ( 21 ), Diabetic nephropathy (DN) ( 22 ), HbA1c ( 6 ), blood pressure ( 8 ), fasting glucose ( 6 ), fasting insulin ( 23 ), Total Cholesterol ( 7 ), Body Mass Index ( 24 ) and smoking ( 25 ). SNPs related to the above confounders ( p < 1×10 –5 ) were excluded to satisfy the MR assumptions.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of DR is complex and includes multiple contributing factors such as oxidative stress, inflammation, angiogenesis, intestinal flora dysregulation, and neurodegeneration ( 4 ). Common risk factors for DR include diabetes course ( 5 ), elevated blood glucose levels ( 6 ), high lipid levels ( 7 ), and hypertension ( 8 ). Despite the extensive research conducted on DR, the mechanisms and risk factors for DR are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…progression and serum lipids, indicating elevated serum levels of LDLC, TG, and TC in patients with DR 29 . Moreover, Mondal et al reported that LDLC levels were 18 , and Zhang et al reported that LDLC and TC levels were 30 associated with intraocular VEGF levels.…”
Section: Et Al Conducted a Systematic Review Of Seven Previous Studie...mentioning
confidence: 99%
“…Some epidemiological studies found no significant association between total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and DR development [ 11 , 12 ]. But other studies observed that triglyceride (TG) and TC levels were significantly associated with DR risk in diabetic patients [ 13 , 14 ]. These discrepant findings could be attributed to measurement errors, uncontrolled confounders, and reverse causality in epidemiological studies [ 15 ], which can induce spurious associations or mask the real risk factors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%